The Effect of Routine Recitation on The Self Healing Ability of Jama'ah in Bandar Klippa Village - Amirul Aziz; Maulana Andi Surya (Fokus)
This research is motivated by daily problems experienced by the community such as stress, anxiety, and depression which are feared to become serious problems if not addressed properly. Therefore, the ability to overcome this is needed, such as self-healing therapy with a religious approach through routine recitation activities. The purpose of this study is to see the effect of routine recitation activities on the self- healing ability of the congregation. This study uses a quantitative method of descriptive correlation. The population of this study was the recitation congregation at the Umar Bin Abdul Aziz mosque, totaling 80 people, the sample was 40 people who were determined by the Slovin formula and selected based on purposive sampling technique. The instrument used was a questionnaire distributed after the congregation finished attending the recitation and in-depth Interviews with several worshipers. Data analysis using IBM SPSS statistical software using simple regression analysis techniques. The results showed that the congregation became calmer and could reduce the level of stress they experienced by being pleased with Allah's decree, smiling, being grateful, praying, thinking positively (husnudzon) and being patient. Thus, it is hoped that every community will participate in recitation activities in order to add insight and train self-healing abilities.